Frequency of Hypoglycemia in Severe Malaria in Children Aged 5 To 144 Months In Kinshasa - Lupemba Jacques, Muziazia; Guan , Fei; Mwamunyi, Mercy Julian; Lei , Jiahui (International Journal of Scientific Research and Management (IJSRM), 2019)
Background: Hypoglycemia is an important complication of severe malaria, especially in children and pregnant women.   In 2017 Kikimi  hospital changed quinine treatment policy from 15 mg/kg loading (plus 10 mg/kg 12-hourly) to 20 mg/kg loading (plus 10 mg/kg 8-hourly) to comply with new WHO guidelines. This presented us with the opportunity to examine whether there was any dose relationship of quinine and hypoglycemia occurrence, in particular, in severe malaria in children from 5 to 144 months.Methods: The study was retrospective of children aged 5 to 144 months admitted to KIkimi hospital with severe malaria between April 2017 and July 2018, before and after the introduction of the new quinine treatment regimen by the WHO. The patient's blood glucose at four hours was measured until intravenous quinine was stopped. Clinical events immediately before or simultaneously with each episode of hypoglycemia (glucose